2021
DOI: 10.1038/s41467-021-21164-w
|View full text |Cite
|
Sign up to set email alerts
|

Particle number-based trophic transfer of gold nanomaterials in an aquatic food chain

Abstract: Analytical limitations considerably hinder our understanding of the impacts of the physicochemical properties of nanomaterials (NMs) on their biological fate in organisms. Here, using a fit-for-purpose analytical workflow, including dosing and emerging analytical techniques, NMs present in organisms are characterized and quantified across an aquatic food chain. The size and shape of gold (Au)-NMs are shown to control the number of Au-NMs attached to algae that were exposed to an equal initial concentration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 64 publications
(33 reference statements)
1
27
1
Order By: Relevance
“…We investigated the stability of the particles in pH 3.5–4 for 14 days by measuring the number of the SMPs that contain Gd and the quantity of the released Gd ions from the particles using single-particle (sp)­ICP-MS . This technique allows the differentiation between the ionic and particulate forms of metals . No Gd ions could be detected after 14 days of incubation, and no significant difference ( t - test , p > 0.05) was found between the number of particles on day 1 and the number of particles on day 14 (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigated the stability of the particles in pH 3.5–4 for 14 days by measuring the number of the SMPs that contain Gd and the quantity of the released Gd ions from the particles using single-particle (sp)­ICP-MS . This technique allows the differentiation between the ionic and particulate forms of metals . No Gd ions could be detected after 14 days of incubation, and no significant difference ( t - test , p > 0.05) was found between the number of particles on day 1 and the number of particles on day 14 (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophobicity of the SMPs was measured after drying a droplet of the particle dispersion on aluminum surface and measuring the contact angle (A KSV Cam 200 contact angle) using Milli-Q (MQ) water at room temperature. The concentration of Gd ions and the number of particles in the exposure media (distilled water) and plant tissues were measured using an ICP-MS (PerkinElmer NexION 350D) operating on a single particle and standard mode. To test the presence of Gd in the particles, PS-SMPs and PVC-SMPs dispersions were deposited on silicon nitride windows (SiNx) and measured using X-ray fluorescence, which is a nondestructive analytical technique used to determine the elemental composition of materials (Supporting Information Section 2) at nm resolution …”
Section: Methodsmentioning
confidence: 99%
“…, ng L −1 range). 21 Recent studies demonstrated the uptake of AuNPs in environmental organisms such as Daphnia magna and zebra fish 22 and Caenorhabditis elegans ( C. elegans ) 23,24 using sp-ICP-MS. The latter studies investigated the uptake by C. elegans of individual AuNP size suspensions ( e.g.…”
Section: Introductionmentioning
confidence: 99%
“…, 30 nm, 60 nm, 80 nm, and 100 nm) and did not consider the uptake from mixtures of AuNPs of different sizes. 23,24 Other studies demonstrated the uptake of AuNPs in the alga Pseudokirchneriella subcapitata using single cell (sc)-ICP-MS. 22,25…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish Danio rerio was used as a model fish, as it is widely distributed in freshwater environments in southern and southeastern Asia, 29–31 is one of the fish species recommended by the OECD TG305, and has been used for many fish bioaccumulation studies of ENMs. 32–35 The uptake and depuration of Ag + were used for comparison, as Ag + is a potential transformation product of AgNPs. The in vivo dissolution of AgNPs was specifically examined by analyzing the dissolved Ag after ultrafiltration of the extracted samples.…”
Section: Introductionmentioning
confidence: 99%